Vegetação dunar: caracterização estrutural de dunas do município de Natal-RN como subsídio para implantação de técnicas de reflorestamernto, recuperação e conservação do ecossistema - Damaso, Patrícia de Paula (2009)
The Brazilian coast has a wide variety of complex environments and ecosystems along the coast, about 80% are represented by sandbanks and dunes. The coastal ecosystems were the first to suffer the impacts man and places, as the very fragile ecosystems, are somehow altered. Are few areas of restinga well as natural features, very few protected in conservation units. Only in the last two decades the Brazilian restinga have been studies that are showing their importance for biodiversity of the country, though its economic importance remains largely unknown. In Rio Grande do Norte in the restinga vegetation and dune environments extend for almost the entire coast. The dunes are distinguished in the coastal landscape of the state due to the exuberance of its forms, heights and coating plants. The dune system is of fundamental importance for the maintenance of coastal urban settlements, especially for the city of Natal, acting on the hydrological dynamics of water table and reducing the effect of wind and movement of grains of sand to the interior and thus avoiding the burial City. However, the ecosystem of restinga and dune environments have been weakened and destroyed according to the intense urbanization and the knowledge of the vegetation of restinga installed on the dunes are still scarce. Thus, the objective of this study was to characterize the structure and floristic composition of vegetation established on a dune in the Dunes State Park Christmas and gather information to develop a model of recovery of the dune ecosystem. This dissertation is composed of 2 chapters, the first being: Structure of the vegetation of the dunes Dunes State Park in Natal, RN with the objective of describing the structure and composition of species of tree-shrub vegetation of restinga dunes of the Parque das Dunas and second: Recovery of degraded areas in a sand dune, which aimed to review the terms and concepts used in the theme of recovery and the techniques for recovery of degraded areas with emphasis on sandy environments and poor in nutrients, reporting some experiences within and external to Brazil the country, mainly in the Northeast and dunes positive and negative aspects that should be followed in building a model to be adopted for the recovery of local dunes